(untitled) (Bangladesh Journal of Medical Science, 2017)
This article describes the neurologic outcomes of 5 survivors of severe perinatal asphyxia at one year of age. All of them developed spastic quadriparesis, microcephaly, growth retardation and developmental delay. The neurologic outcomes correlated with the sites of brain injury. Bangladesh Journal of Medical Science Vol.16(1) 2017 p.174-177